If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -4 = 2(3x + -1) Reorder the terms: -4 + x = 2(3x + -1) Reorder the terms: -4 + x = 2(-1 + 3x) -4 + x = (-1 * 2 + 3x * 2) -4 + x = (-2 + 6x) Solving -4 + x = -2 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -4 + x + -6x = -2 + 6x + -6x Combine like terms: x + -6x = -5x -4 + -5x = -2 + 6x + -6x Combine like terms: 6x + -6x = 0 -4 + -5x = -2 + 0 -4 + -5x = -2 Add '4' to each side of the equation. -4 + 4 + -5x = -2 + 4 Combine like terms: -4 + 4 = 0 0 + -5x = -2 + 4 -5x = -2 + 4 Combine like terms: -2 + 4 = 2 -5x = 2 Divide each side by '-5'. x = -0.4 Simplifying x = -0.4
| 12x=11x-14x | | x+(.07*x)=50 | | 2(3+2x)-3=27 | | .02(.8x)+.05x=119.6 | | sqrt(x-1)+x=7 | | 2.5+.075p=.01p | | 5ln(2x-2)+10=0 | | X^2+13x-31=7x-4 | | 20x+10=5*20 | | 2.1x-8.1=3.16-5.4x | | 2p^2/5-p^1/5-1=0 | | H(t)=-10t^2+10t+24 | | .05x+.06(3x)=943 | | 5y-3+y+29=5y+30-1y | | .6n-.6=6n+1.3 | | 3x+20=8x-40 | | 6g+18=9g-25 | | -7-7(4x+8)=-175 | | a-a^1/2-6=0 | | 3x+20=4x-5 | | a-a^1/2-6= | | 9r^2=18 | | g−3/7=2/7 | | 12-3(3-3x)=6x | | -235=.05(x)-.06(x) | | |x/2-3|-5-2 | | 3z/10-9=-8 | | 7a-1=4(3a+6) | | 14x-9=13x+51 | | 3/x-2=1/x | | 4/56 | | 3(4x+5y)=12 |